Experimental tests and numerical simulations to even out the flue gas and fly ash distribution in the flue channels of the BB-1345 boiler in the Pątnów II Power Plant - Lewtak, Robert; Glot, Beata; Świątkowski, Bartosz (Instal, 2023)
The purpose of the work was to diagnose the causes of uneven flow of flue gas and fly ash in the flue gas ducts of the BB-1345 boiler electrostatic precipitator in the Pątnów II Power Plant and to present a method of solving the above-mentioned problem. Work began with a series of measurements carried out in the flue gas ducts above and below the rotary air heater (RAH) from the front and rear sides of the boiler. The aim of the measurements was to determine the distribution of temperature, velocity and relative pressure of the exhaust gas as well as the concentration of fly dust at selected points. Then, geometrical models of the flue gas channels were prepared together with the RAH for the current state and the proposed concepts of changes. The geometry was made on the basis of the technical documentation provided by the power plant operator and took into account the ducts and RAH on the side of flowing flue gases without insulation. Numerical calculations were made using the Ansys FLUENT software and were carried out for the current state and the proposed concepts of changes. The calculations of the current state were made for two variants, i.e. the variant without taking into account air intake to the exhaust gases and the variant taking into account the intake of air into the exhaust gases. Taking into account the air suction resulted in obtaining a dust distribution on the left and right side convergent with the measurements. The suction air flow was pushing the dust towards the rear RAH cradle collecting the dust to the right exhaust duct. The dust-pushing effect was especially visible for the suction over the RAH rotor, due to the air “sliding” effect on the upper side of the RAH rotor. On the other hand, the air flowing from the suction under the RAH was directed to a lesser extent into the exhaust gas channel and, having no physical obstacle in the form of a rotor, mostly flowed downwards. Taking into account the air suction to the exhaust gases turned out to be of key importance in order to correctly model the actual conditions of the exhaust and dust separation into the right and left channels under the RAH. On the basis of the simulation of the existing state, the cause of the flow disturbances was determined and the concept of changes recommended for installation on the exhaust gas ducts was determined, resulting in a uniform distribution of exhaust gases. During the analyzes of the modified system, four concepts of changes in the elements directing the exhaust gases in the space under the RAH in order to equalize the flow of exhaust gases were developed. As a result, a concept was selected that consisted in the installation of a vertical partition dividing the exhaust duct under the RAH into the right and left sides. Taking into account that the numerical calculations showed the accumulation of dust at the rear wall, the selected concept was further modified with adjustable elements regulating the dust and gas stream. In the final stage of work, a preliminary structural design of the selected modernization variant was prepared.
Keywords: rotary air heater; boiler; flue gas ducts; numerical simulations